Performance of Broiler Chickens Fed 8% Crude Fibre Diets at Three Energy Levels With or Without Enzyme During the Starter and Finisher Phases - Salami , R.I.; Odunsi, A.A. (International Journal of Poultry Science, 2019)
Background and Objective: Optimal inclusion levels of Crude Fibre (CF) and exogenous enzymes in poultry diets have beneficial effects on growth performance indices and feed cost per unit weight gain. This study was, therefore, conducted to evaluate the production performance and economy of unsexed Obamarshal broiler chickens fed ca 8% CF diets at three energy levels with or without Roxazyme®G2G supplementation during the starter and finisher phases. Materials and Methods: One hundred and forty-four day-old unsexed Obamarshal broiler chicks were divided into six treatments at 24 birds each with three replicates per dietary treatment and fed for 28 days each for the starter and finisher phases with ca 8% CF diets at 2600, 2800 and 3,000ME (kcal kg–1 diet) with or without enzyme. Roxazyme®G2G was incorporated at 0 and 200 mg kg–1 diet per energy level to produce six diets labeled A, B, C, D, E and F in ascending order of energy and enzyme levels. Live weight, average daily gain (ADG), feed intake, feed conversion ratio (FCR), protein intake, protein efficiency ratio (PER), calorie intake, fibre intake, water intake, water intake: feed intake, water intake: weight gain, faecal output and mortality rate were evaluated using standard methods. Data were analysed using 2×3 factorial arrangement and according to one-way Analysis of Variance. Means were separated with Duncan’s Multiple Range Test at p